2018
DOI: 10.1089/thy.2017.0567
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Urinary Cotinine-Verified Active and Passive Smoking with Thyroid Function: Analysis of Population-Based Nationally Representative Data

Abstract: Active and passive smoking were associated with decreasing serum TSH levels and a lower risk of SCH in a Korean population. These associations might be related to lower urinary iodine levels in active smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…This study demonstrated that the median UIC in smokers was higher than in nonsmokers, but not with statistical significance. Kang et al reported that active smokers had significantly lower iodine levels than passive smokers and nonsmokers . Regardless of smoking status, both groups were associated with decreasing serum TSH levels, which might be related to lower urinary iodine levels .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This study demonstrated that the median UIC in smokers was higher than in nonsmokers, but not with statistical significance. Kang et al reported that active smokers had significantly lower iodine levels than passive smokers and nonsmokers . Regardless of smoking status, both groups were associated with decreasing serum TSH levels, which might be related to lower urinary iodine levels .…”
Section: Discussionmentioning
confidence: 97%
“…Kang et al reported that active smokers had significantly lower iodine levels than passive smokers and nonsmokers . Regardless of smoking status, both groups were associated with decreasing serum TSH levels, which might be related to lower urinary iodine levels . It was unclear whether smoking decreased the urinary iodine levels until now.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of smoking on hypothyroidism were inconsistent in different studies which may be affected by iodine nutrition. A study in an iodine-deficient area in India and an iodine-sufficient area in Korea also found that smoking reduced serum TSH levels 28 29. Research by Park et al also showed that smoking reduced TSH levels at different iodine levels and smoking status was not associated with iodine intake 30.…”
Section: Discussionmentioning
confidence: 93%
“…In 1991, Feldman J et al reported that passive smoking can affect lipid metabolism in adolescents [20]. Subsequently, several studies related to endocrine and metabolic diseases were reported [8,21]. However, the results from studies on the effects of passive smoking on the prevalence of prediabetes and T2DM have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%